Effect of Alcoholic Extract of Caroob Fruits Ceratonia siliquaon The Physiological and Histological Characteristic of Ovaries of Swiss Rat Ratus ratis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This experiment was designed to evaluate the effect of  alcoholic extract of caroob  Fruits Ceratonia siliqua on the histological features of female Swiss rat ovaries. The results were showed that high concentration( 300 mg/kg) of alcoholic extract improved the characteristics of ovaries by increasing volumes and numbers of growing follicles primordial, primary and secondary follicles. In addition, there were increasing in numbers and volumes of corpus luteum and there were increasing in ovaries weights. Other experimental animals group were treated by the lower concentration of caroob  Fruits Ceratoniasiliqua(100 mg/kg) and microscopically section showed that the ovary cortex contained fewer numbers of growing follicles and corpus luteum.